Taboo Words (Haba Geutham) As A Morals In Language and Psychological Effect in Pidie Community - Vera Wardani (Jurnal Serambi Ilmu, 2021)
This study aims to describe taboo words (haba geutham) as a form of languageadab and the impact of psychological influences on Pidie community activities.This type of research is field research using a qualitative approach. The methodused is descriptive-analytical. The data of this research are taboo words (habageutham) as a form of language adab and the impact of psychological influenceson the activities of the Pidie community. The data source of this research isinformants, namely the people who live in Pidie district. The data was collectedusing structured interview techniques which are supported by inducementtechniques. The data analysis technique used is the stage analysis technique,selecting data, describing the entire data, grouping the data, and analyzing thedata. The results of the research found were taboo words (haba geutham) as aform of language adab in Pidie community activities including, (1) taboo languageof words relating to animals, (2) taboo language regarding spirits (3) taboolanguage -words relating to disease, (4) taboo language of words relating tofarming activities, (5) taboo language of words relating to hunting activities, (6)taboo language of words relating to nighttime, (7) taboo language words relatingto the tradition of marriage, (8) taboo language of words relating to body organs,(9) taboo language of words relating to femininity, (10) taboo language of wordsrelating to the genitals and sexual organs, ( 11) taboo language of words relatingto sexual activity, and (12) taboo language of words relating to certain words.Regarding the impact of the psychological influence of taboo words (habageutham) on community activities Pidie has a negative impact because it is causedby speech, (1) taboo words (haba geutham) because of fear, (2) taboo words (habageutham) ) because they feel uncomfortable or uncomfortable, (3) taboo words(haba geutham) because they feel impolite and impolite, and (4) taboo words(haba geutham) are contrary to religion.